Uji Validitas Kriteria Time Up and Go Test (TUG) Sebagai Alat Ukur Keseimbangan pada Lansia (Lembaga Penerbitan Universitas Esa Unggul, 2009)
Background: advanced age the total more increase, in old age will happen body function depreciation, fall to be one of main problem in old age, balance is the root cause older fall, balance measuring instrument existence helps rehabilitation program and preventionÂ old age fall. Aim: detect criteria validity time up and go test /tug (measuring instrument not yet standard) that compared with dynamic gait index / dgi (standard measuring instrument). plan: watchfulness observasional (survey) with measures balance old age use two measuring instrument that is dgi and tug. subject: 23 (twenty three) lansia that house wreda dharma bhakti Surakarta and fulfil criteria inklution and eksklution. execution: l old age measuresed fungs balance with dgi and continued with tug. execution dgi consist of 8 commands that is (1) walk with normal speed, (2) walk with speed change, (3) walk with head rotation horizontal, (4) walk with rotation head vertical, (5) walk and rolling in one pillar, (6) walk to pass by hindrance, (7) walk around hindrance, (8) walk uphill and downstair. 8 commands dgi measuresed with 4 criterias that is normal, light and heavy. Execution tug l old age stand from sit, then walk as far as 3 meters, rolling, walk embali aim chair and sit to return. Data analysis: use correlation test person (normal data distribution) to detect balance result correlation that measuresed with dgi and tug. Result: there balance result correlation that measuresed with dgi and tug (p<0,5, big correlation coefficient r = -0,754 (berkorelasi strong, negative connection character. Conclusion: tug fulfil criteria validity as a means balance in old age. Tug serve the purpose of balance measuring instrument because valid, reliabel and efficient.Keywords: Criteria validity, Menamic Gait Index, Time Up and Go Test